The Clinical and Radiological Outcomes of Surgical Decompression in Older Patients with Lumbar Spinal Stenosis - Şevki Gök; Merih İş; Alp Karaaslan; Recep Başaran; Neşe Keser; Mehmet Zafer Berkman (Boğaziçi Tıp Dergisi, 2022)
INTRODUCTION: Lumbar spinal stenosis (LSS) is 'a clinical syndrome of the buttock or lower extremity pain, which may occur with or without back pain, associated with diminished space available for the neural and vascular elements in the lumbar spine.' This study aims to analyze the clinical and radiological outcomes of lumbar decompression in patients with degenerative LSS. METHODS: The patients with degenerative LSS in the Department of Neurosurgery of Haydarpasa Numune Training and Research Hospital were included retrospectively. The radiological evaluations were measured with the extreme PACS system (2010) by magnetic resonance imaging. The clinical outcomes were evaluated with visual analog score (VAS) and Japanese orthopedic association (JOA) scores. Odom's criteria were used for outcomes. RESULTS: Thirty-five patients over 65 years old with degenerative LSS were underwent posterior decompression surgery. Of the participants, 40% (n=14) were male and 60% (n=21) were female. The mean age is 63.34+-8.08. The area measurements, modified area measurements, AP diameter measurements of the right and left lateral recess, right and left lateral transverse AP diameter measurements, and AP diameter measurements of the right and left neural foramen were improved after surgery. VAS and JOA scores were good after surgery. Fourteen patients had an excellent result, 12 patients had a good result, and nine patients had a fair result according to Odom's criteria. DISCUSSION AND CONCLUSION: Improvements in the VAS and JOA scores are prominent after surgery. Foraminotomy and expansion of the lateral recess during surgery increased the quality of life and improved post-operative radiologic parameters in over 65 years of age with degenerative LSS.